Sustainable plastics : environmental assessments of biobased, biodegradable, and recycled plastics - Greene, Joseph P., 1961- (Wiley, 2014)
"Providing guidelines for implementing sustainable practices for traditional petroleum based plastics, biobased plastics, and recycled plastics, Sustainable Plastics and the Environment explains what sustainable plastics are, why sustainable plastics are needed, which sustainable plastics to use, and how manufacturing companies can integrate them into their manufacturing operations. A vital resource for practitioners, scientists, researchers, and students, the text includes impacts of plastics including Life Cycle Assessments (LCA) and sustainability strategies related to biobased plastics and petroleum based plastics as well as end-of-life options for petroleum and biobased plastics"--Resumé vydavatele
Keywords: biodegradovatelné polymery; plasty -- environmentální aspekty; environmentální chemie; biodegradace; recyklované materiály; biodegradable polymers; plastics -- environmental aspects; environmental chemistry; biodegradation; recycled materials; monografie; monographs